1997
DOI: 10.1038/sj.bjp.0701314
|View full text |Cite
|
Sign up to set email alerts
|

Study of the in vivo and in vitro cardiovascular effects of a hydralazine‐like vasodilator agent (HPS‐10) in normotensive rats

Abstract: 1 In this work, the cardiovascular e ects of HPS-10, a new vasodilator agent, were studied in rats. 2 In conscious normotensive rats, oral administration of HPS-10 (4 ± 9 mg kg 71 ) produced a doserelated and long-lasting fall in systolic arterial blood pressure (ED 30 of 5.32 mg kg 71 ), accompanied by an increase in heart rate (ED 30 of 8.43 mg kg 71 ). This tachycardia was totally inhibited by pretreatment with (+)-propranolol (10 mg kg 71 , p.o.). In rat isolated rubbed aorta, HPS-10 (0.1 ± 1 mM) non-compe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 24 publications
3
33
0
Order By: Relevance
“…In our experiments, the rat aortic rings lacked spontaneous activity, as we have reported previously (Orallo, 1997). The resting tone was unaffected by DMSO (0.14-1.40 mM), atropine (10 M), yohimbine (1 M), and t-RESV (1-10 M) in endotheliumdenuded and/or intact rat aortic rings (n ϭ 5; p Ͼ 0.05; data not shown).…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…In our experiments, the rat aortic rings lacked spontaneous activity, as we have reported previously (Orallo, 1997). The resting tone was unaffected by DMSO (0.14-1.40 mM), atropine (10 M), yohimbine (1 M), and t-RESV (1-10 M) in endotheliumdenuded and/or intact rat aortic rings (n ϭ 5; p Ͼ 0.05; data not shown).…”
Section: Resultssupporting
confidence: 52%
“…Vascular rings were prepared from the aortas of male Wistar rats weighing 250 to 300 g, essentially as described elsewhere (Orallo, 1997). In addition, contraction/relaxation studies were performed following the general method indicated in Orallo et al (1998).…”
Section: Methodsmentioning
confidence: 99%
“…However, previous reports have shown that t-RESV directly relaxes rat aortic smooth muscle [8,9] (see Section 1). These discrepancies could be due to the following reasons: i) A different sensitivity to RESV of the A7r5 cloned cell line compared to the rat aortic smooth muscle cells (RASMCs) isolated from the medial layer of rat aorta (for detailed method of preparation, see [19]). In order to exclude or confirm this possibility, further investigations are currently being conducted in our laboratory to establish whether RESV also induces increases in [Ca 2+ ] i in RASMCs.…”
Section: +mentioning
confidence: 99%
“…Vascular rings were prepared from the mesenteric arteries of male Wistar rats, body weight of 250 -300 g, essentially as described elsewhere (19). The studies reported in this work have been carried out in accordance with the European regulations on the protection of animals, the Declaration of Helsinki, and / or the Guide for the Care and Use of Laboratory Animals as adopted and promulgated by the United States National Institutes of Health.…”
Section: Methodsmentioning
confidence: 99%